MPI CEO CHAMIL WARIYA RECEIVES PhD DEGREE RESEARCHING ON PM SPEECHES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, May 2015 The Chief Executive Officer of the Malaysian Press Institute (MPI), Datuk Chamil Wariya received the Doctor of Philosophy degree (PhD) in the field of Communication at the recently concluded Universiti Sains Malaysia (USM) 51st Convocation.